Deliberative qualities in televised election debates: the influence of the electoral system and populism. Issue 6 (18th September 2020) - Marien, Sofie; Goovaerts, Ine; Elstub, Stephen
Abstract: Concerns are raised repeatedly about the quality of televised debates. Both a country's electoral system and the presence of populist candidates have been argued to influence the deliberative qualities of these debates. By using an extended version of the Discourse Quality Index, this study conducts a content analysis of 12 televised election debates in Germany, the Netherlands and the United Kingdom between 2009 and 2015. Against expectations, results show that politicians in multiparty systems do not justify their policy positions more and are not more respectful in the televised debates. Rather, this study uncovers a clear populist challenge to key deliberative debate qualities across party systems. Left- and right-wing populist politicians adopt more positions without proper justification, and the presence of right-wing populists in the televised debates increases the number of disrespectful interactions, lowering the deliberative qualities of the televised debates in different electoral contexts.